The Long-Term Impact of High School Financial Education: Evidence from Brazil - Bruhn, Miriam; Garber, Gabriel; Koyama, Sergio; Zia, Bilal (The Review of Economics and Statistics, 2025)
Abstract As the financial system expands to new clients and services, countries are promoting financial education, with unknown long-run returns. In 2011, we studied the short-run impact of a comprehensive financial education program through a randomized controlled trial with 892 high schools in Brazil. This paper uses administrative data for 16,000 students over the next nine years to measure the program's long-term impact. We find that treatment students are less likely to borrow from expensive sources or to make delayed loan repayments than control students. The program also caused students to shift from formal jobs to microenterprise ownership.